The Iranian Foreign Policy: Between Continuities and Change: An Analysis of the Syrian Case - Falih Hassan, Nisreen (Journal of College of Education, 2021)
After the Islamic Revolution of 1979, "Iran" pursued an isolationist foreign policy with an anti-imperialist rhetoric. However, with the start of the "Iran-Iraq War", Iran turned its isolationist "foreign policy" into a multilateral policy, and as a result of the changes in the balance of power that followed the attacks. 9/11, Iran “relaunched an ideological-oriented foreign policy. Although the conflicting rhetoric in "Iranian foreign policy" began to decline during the "era of President Rouhani," but the "foreign policy" directed towards ideology and identity is still continuing. Therefore, Iran’s "foreign policy" towards Syria was formed according to determinants such as "Iranian national security." The formation of the Shiite crescent, geopolitics, and the regional balance of power.